Contribution to the genus Anomala Samouelle, 1819 (Coleoptera: Scarabaeidae: Rutelinae) of China and adjacent regions. Part I: descriptions of two new species and remarks on four species - Zhao, Ming-Zhi (Zootaxa, 2021)
Two new species of the genus Anomala Samouelle, 1819 are described: A. dianopicta Zhao, new species from Yunnan and A. huangyuzhoui Zhao, new species from Hunan. New distributional records for Anomala bella Arrow, 1917, A. blaisei Ohaus, 1914, A. cyanipennis Lin, 1999 and A. granuliformis Lin, 1996 are presented.